Stakeholder involvement and preferences in landscape protection decision-making: a systematic literature review - Li, Yue; Abu Bakar, Nor Azlina; Ismail, Nor Atiah; Mohd Ariffin, Noor Fazamimah; Mundher, Riyadh (Frontiers Media SA, 2024)
Stakeholder involvement and preferences are pivotal in the decision-making process for landscape protection within a specific context. However, many decisions regarding landscape protection options still rely on management choices with little or no consideration of all stakeholders. Previous scholars emphasized the importance of establishing an integrated framework to gain an adequate understanding of the process of stakeholders’ decision-making in landscape protection. Therefore, a systematic literature review was conducted on the topic of stakeholders’ involvement and preferences in landscape protection decision-making. This review included research articles published from 2013 to 2023 using two databases and registers, namely, Science Direct and Google Scholar. A total of 110 research articles were identified and qualified for review based on the screening requirements, with an additional 15 documents for theories and backgrounds to provide a better understanding and outcomes for the study. The results of this study were organized based on concepts from the resulting research articles and were integrated to propose a conceptual framework for Stakeholders’ involvement and preferences in landscape protection. Additionally, this study’s findings indicate the significance of incorporating diverse stakeholders and their preferences in landscape protection processes to ensure awareness of inclusivity in decision-making and secure long-term support.